Prototype Pendeteksi Amoniak Pada Ruang Berbasis Microkontroler - Muhamad Sidik; Nailin Niklis (STEKOM PRESS, 2021)
This Research is generally aimed at designing a system that can solve problems at Hotel Oyo Jakarta Selatan. In addition to the use of bathroom tools, there is a need for a gas controller in the bathroom space, especially ammonia gas and other gas in the bathroom. The bathroom control system at Hotel Oyo Jakarta Selatan is currently ineffective, in the use of the bathroom tools to hotel guests and hotel staff. The reseach method used by researcher is The research step begins with research and information gathering, then planning and developing the initial form of the product or system, and field testing the feasibility of the system or product, if there is a revision, it can be developed further before conducting the main field test. . Based on the research results, monitoring ammonia gas in rooms based on a microcontroller can be a solution for the Oyo South Jakarta hotel in monitoring rooms, both from guests or hotel employees more effectively and efficiently , and to facilitate the management of existing bathroom rooms in the Hotel Oyo Jakarta Selatan